The effect of information asymmetry, budget emphasis, individual capacity and self esteem on budget performance with budgetary slack as a mediation variable and budget participation as a moderating variable in regional apparatus organizations in Berau district - Munawaroh, Siti; Ratnawati, Tri; Pristiana, Ulfi (Edelweiss Applied Science and Technology, 2024)
This study aims to analyze the Influence of Information Asymmetry, Budget Emphasis, Individual Capacity and Self Esteem on Budget Performance with Budgetary Slack as a Mediating Variable and Budget Participation as a Moderating Variable in Regional Government Organizations in Berau Regency. The research design uses an explanatory research approach, with the sample being the sample in this study, namely the regional apparatus organization involved in the process of preparing, implementing and accounting for the budget. The total population and sample are 141 people consisting of 47 regional apparatus organizations in Berau Regency. The data collection method is a survey using a questionnaire, and the analysis technique used is Structural Equation Modeling (SEM).